(untitled) (Research, Society and Development, 2020)
Performance indicators, in addition to measuring instruments, are allies of the management process in the quest to achieve organizational results. The present is a theoretical essay that has a qualitative approach, being exploratory and bibliographic research. The objective of the article is to reveal a strategic and managerial utility for the indicators, in order to serve as a base to support choices in public management, making them more assertive. For this, some classifications of the institutional performance indicators are presented, in addition to assessing their adequacy and the existing challenges for the necessary improvement in administrative management. The strategic and managerial utility for the indicators is revealed as a basis for supporting decisions, making them assertive.